Family Policies and Fertility: Parents' Parental Leave Use, Childcare Availability, the Introduction of Childcare Cash Benefit and Continued Childbearing in Norway - Trude Lappegård (Statistics Norway, Research Department, 2008)
We address the relationship between family policies and fertility in Norway, including three somewhat different policies: parental leave, formal childcare, and the childcare cash benefit. Norwegian family policy has been considered dualistic, giving priority to both dual-earner support and general family support. Our data are administrative register data covering the period 1995-2002. The analysis shows that policies that promote father involvement in childcare and gender equality are positively associated with timing of second births, while policies giving more general family support are positively associated with timing of third births. The so-called "double-tracked" family policy seems to apply to different couples in a positive matter. An important insight of this paper is that both policies designed to improve reconciliation of work and family, and policies designed to improve childcare choices for parents, are indeed popular; however, in terms of fertility outcomes, there is wide heterogeneity in how they respond to the policies.
Keywords: J13; J18; 330; fertility; family policy; parental leave; formal childcare; the childcare cash benefit